Echoes of Scripture in the letter of Paul to the Colossians - Beetham, Christopher A. (Biblical Interpretation Series, 2008)
While the use of the Old Testament in the New Testament has captured the attention of biblical scholars over the years, no study has been devoted to the presence of Scripture in Colossians, largely because there are no explicit quotations in Colossians. With the introduction of literary intertextuality into the discipline, however, scholars have begun to devote more attention to the NT authors' less explicit references to Scripture, often labelled as 'allusions' and/or 'echoes.' Scholars, however, continue to debate what constitutes an allusion or echo, or how one validates a given proposal as such. This study proposes new definitions of these terms and offers a methodology on how to detect and validate them, using Colossians as a test case.